Non‐Peutz‐Jeghers syndrome‐associated ovarian sex cord tumor with annular tubules: Report of a malignant case. Issue 2 (29th December 2015) - Han, Ying; Li, Shumin; Wu, Lingying; Zhang, Xun; Cao, Dengfeng
Abstract: A sex cord tumor with annular tubules (SCTAT) is a rare but distinctive subtype of sex cord stromal tumor of the ovary. Its clinical features depend on an association with Peutz‐Jeghers syndrome (PJS). SCTAT associated with PJS typically manifests as bilateral, multifocal, and small lesions and is clinically benign. In contrast, SCTAT not associated with PJS often manifests as a unilateral large mass and 20% of such tumors have malignant potential. Most patients with SCTAT are diagnosed at stage I, and metastasis is rare. Here we present a case of malignant SCTAT of stage III A1(ii) (retroperitoneal lymph node metastasis, largest dimension of metastasis >10 mm) in a 14‐year‐old girl without PJS.